IMPLEMENTASI PENILAIAN PEMBELAJARAN DI TAMAN PENDIDIKAN AL-QUR’AN (TPA) HIDAYATULLAH SAMBILEGI LOR YOGYAKARTA - Khalimah, Siti (Al-ATHFAL: Jurnal Pendidikan Anak, 2024)
The purpose of this research is to identify the methods of using learning assessments at the Al-Qur'an Education Park (TPA) Hidayatullah Sambilegi Lor Yogyakarta, as well as to find supporting and inhibiting factors for the assessment. This research is a type of qualitative study, and the aim of this research is to explore phenomena, evaluate data, and correctly interpret the results. Interviews, observations, and documentation are the research techniques used. TPA Hidayatullah conducts learning assessments in three stages: daily assessments, monthly assessments, and semester assessments. The research results show that the children of TPA Hidayatullah received good grades, although there were also some who did not perform well because they did not understand the material being taught. Teamwork and the availability of adequate facilities are supporting factors in the assessment of the learning of TPA Hidayatullah children, while the inhibiting factor is the teachers' lack of understanding of how to use certain instruments. Keywords:  Implementation, Assessment, Quranic Education Park (TPA)